2023
DOI: 10.1021/acscatal.3c02525
|View full text |Cite
|
Sign up to set email alerts
|

Photoinducing Different Mechanisms on a Co-Ni Bimetallic Alloy in Catalytic Dry Reforming of Methane

Abstract: Photothermal catalytic dry reforming of methane (DRM) is a promising process for simultaneous solar energy conversion and fossil fuel upgrading; however, its mechanistic difference from thermocatalysis has not been much investigated. Herein, we report a comprehensive mechanistic investigation of bimetal NiCo/SiO 2 in photothermo-and thermocatalytic DRM. Co substitution in Ni/SiO 2 poses a suppressing effect on thermocatalysis, while a promotion effect emerges after light irradiation. In situ diffuse reflectanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Recently conducted research has demonstrated that the incorporation of light irradiation into conventional thermal catalytic systems could significantly enhance CO 2 conversion efficiency under mild conditions, including various strategies of photothermal catalytic CO 2 reduction by H 2 , CH 4 , and H 2 O, establishing it as a rapidly advancing and captivating field of study. Therefore, it is imperative to develop efficient catalysts for photothermal CO 2 conversion. So far, various heterogeneous catalytic systems have already been reported with supported plasmonic metal nanoparticle-based catalysts exhibiting promising potential. , Upon exposure to light irradiation, the localized surface plasmon resonance (LSPR)-induced hot electrons over metal nanoparticles directly injected into the antibonding orbitals of adsorbed molecules, facilitating the activation of adsorbed species and reducing energy barriers in key reaction steps. , In addition, the decay of electromagnetic fields produced around the metal/support interfaces arising from the LSPR effect would effectively elevate the local temperature of the catalyst, thereby promoting reaction kinetics. Despite a lot of pioneering work on various plasmonic metal/semiconductor systems, such as Ru/H x MoO 3– y , Ir@UiO-66, and Co/La-TiO 2 , unfortunately, the unsatisfying light utilization capacity and limited catalytic behavior based on inert supports with relatively wide bandwidth still result in low efficiency for CO 2 conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Recently conducted research has demonstrated that the incorporation of light irradiation into conventional thermal catalytic systems could significantly enhance CO 2 conversion efficiency under mild conditions, including various strategies of photothermal catalytic CO 2 reduction by H 2 , CH 4 , and H 2 O, establishing it as a rapidly advancing and captivating field of study. Therefore, it is imperative to develop efficient catalysts for photothermal CO 2 conversion. So far, various heterogeneous catalytic systems have already been reported with supported plasmonic metal nanoparticle-based catalysts exhibiting promising potential. , Upon exposure to light irradiation, the localized surface plasmon resonance (LSPR)-induced hot electrons over metal nanoparticles directly injected into the antibonding orbitals of adsorbed molecules, facilitating the activation of adsorbed species and reducing energy barriers in key reaction steps. , In addition, the decay of electromagnetic fields produced around the metal/support interfaces arising from the LSPR effect would effectively elevate the local temperature of the catalyst, thereby promoting reaction kinetics. Despite a lot of pioneering work on various plasmonic metal/semiconductor systems, such as Ru/H x MoO 3– y , Ir@UiO-66, and Co/La-TiO 2 , unfortunately, the unsatisfying light utilization capacity and limited catalytic behavior based on inert supports with relatively wide bandwidth still result in low efficiency for CO 2 conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several recent studies have shown the hot carriers’ potential in mitigating the formation of unwanted byproducts, especially in the context of photo-thermal dry reforming of methane. 145,146…”
Section: Photo-thermal Catalytic Nh3 Synthesismentioning
confidence: 99%
“…Indeed, several recent studies have shown the hot carriers' potential in mitigating the formation of unwanted byproducts, especially in the context of photo-thermal dry reforming of methane. 145,146 When it comes to thermal effects, the photo-induced heat at the nanoscale provides high temperatures at the active sites in a more efficient way compared to traditional thermo-catalysis. These elevated temperatures translate into catalytic activities that are several orders of magnitude above those obtained with conventional photo-catalysis, mainly due to both the improved reaction kinetics and energy-mass transfer.…”
Section: Photo-thermal Catalytic Nh 3 Synthesismentioning
confidence: 99%
“…Photothermal catalysis and organic degradation PC is a common method used in organic matter degradation, and the efficiency of photocatalytic pollution degradation can be further improved by using the photothermal effect [148,149] . Huang et al introduced oxygen vacancies into BiOI nanosheets (named BiOI-8) with low concentration nitric acids and applied them to photocatalytic degradation of formaldehyde [150] .…”
Section: Photothermal Catalysis and Co 2 Reductionmentioning
confidence: 99%